MEDICAL SUPPORT IN THE COMPREHENSIVE TREATMENT OF GENERALIZED PERIODONTITIS (LITERATURE REVIEW) - І.І. Sokolova (Український стоматологічний альманах, 2025)
The purpose of the study is to analyze the scientific literature on the means and approaches to drug support in the complex treatment of generalized periodontitis.